Analytical evaluation of nonlinear distortion effects on multicarrier signals - Araújo, Teresa; Dinis, Rui (CRC Press, Taylor & Francis Group, 2015)
This book examines the nonlinear distortion of multicarrier signals. First, it outlines the basic principles of multicarrier transmission and multicarrier-based systems. Next, it presents a unified approach to well-known analytical results on memoryless nonlinearities that takes advantage of the Gaussian behavior of multicarrier signals. This is followed by a theoretical study of the accuracy of the Gaussian approximation usually used for multicarrier signals. Finally, a study of the performance of some multicarrier-based systems in the presence of different types of nonlinear devices is presented